Synthesis of a fractional-order PIλDμ-controller for a closed system of switched reluctance motor control - Tytiuk, Valerii; Chornyi, Oleksii; Baranovskaya, Mila; Serhiienko, Serhii; Zachepa, Iurii; Tsvirkun, Leonid; Kuznetsov, Vitaliy; Tryputen, Nikolay (Eastern-European Journal of Enterprise Technologies, 2019)
The relevance of creating high-quality control systems for electric drives with a switched reluctance motor (SRM) was substantiated. Using methods of mathematical modeling, transient characteristics of the process of turn-on of SRMs with various moments of inertia were obtained. Based on analysis of the obtained transient characteristics, features of the SRM turn-on process determined by dynamic change of parameters of the SRM during its turn-on were shown. Low accuracy of SRM identification using a fractionally rational function of rat34 class was shown. Regression coefficient of the resulting model was 85 %. Based on analysis of transient characteristics of the SRM turn-on process, a hypothesis was put forward about the possibility of identifying the SRM by means of a fractional-order transfer function. Using the methods of mathematical modeling, transient characteristics of the process of turning-on the SRMs with various moments of inertia were obtained. Using the FOMCON MATLAB Toolbox, identification of the SRM turn-on process with the help of a fractional-order transfer function of second order was performed. Regression coefficient of the resulting model was 93–96 %. For the obtained fractional-order transfer functions, a method of synthesis of a fractional-order PIλDμ controller optimized in terms of minimum integral square error of the transition function of the closed system of fractional-order control of objects was implemented. The FOMCON MATLAB Toolbox was used for synthesis of the PIλDμ controller. Comparative analysis of the SRM turn-on processes in both open and closed control systems with a classical integer-order PID controller and with a fractional-order PIλDμ controller was made. Use of the fractional-order PIλDμ controller in comparison with the classical integer-order regulator makes it possible to reduce overshoot from 13.3 % to 2.64 %, increase speed of the closed ACS, decrease regulation time from 1.48 s to 0.53 s while reducing variability of transient characteristics. The study results can be used to improve performance of closed systems for controlling angular velocity of the SRM